The eastern border of the European Union. Current scenario and future strategies. - Marcu, Silvia (Anales de Geografía de la Universidad Complutense, 2006)
During the 20th century, the European continent has been through a process of important geopolitical and cultural change. Contacts between different forces not always led to a greater convergence. Persisting differences are reflected in the variety and intensity of the current relations between the European Union and its new neighbours, and the contacts established between these states that now share the border with the EU. The purpose of this article is to introduce those countries which border the European Union from the East, namely Ukraine and Moldova as well as regional and global problems this countries are facing in the wider context of geopolitics, security and stability. Attention is being drawn to the role which the EU is playing at present and might play in the future, in terms of the development of the aforementioned countries, which have declared their entry into the NATO and EU as a long-term objective.
Keywords: European Union; Strategy; Border; Ukraine; Moldova